Hamlet – With and Without the Prince:: Terrorism at the Outbreak of the First World War - Wilson, Keith (Journal of Conflict Studies, 2007)
Abstract While the assassination of Archduke Franz Ferdinand in Sarajevo on 28 June 1914 helped to set in train a series of reactions by various governments that led to the outbreak of the First World War, the story neither begins nor ends there. From an historian’s perspective, this simple ‘cause and effect’ formula does not do justice to what is a far more complex story. This article assesses that event’s place in history by situating it within a wider context. It explores how the assassination interacted, first with the Byzantine geopolitics of the Balkans and the Austro-Hungarian Empire, and then with the weltanschaung of Kaiser Wilhelm II of Germany, to become a catalyst for war. If the events of 1914 tell us anything about the nature of terrorism they first illustrate ‘the law of unintended consequences.’ Terrorists are not always able to control the outcome of their actions, which depends on how others react. The Archduke’s assassins did not intend to start a global war by killing him. Unwittingly, they provided the Kaiser with the pretext for a war that he had sought for two years. Second, and flowing from that, it is clear that the significance of terrorist campaigns and actions cannot be understood in isolation from the political contexts in which they occur. Finally, in their desire to strike a blow against a ‘foreign’ authority, one can see that the motives and actions of the Archduke’s attackers were analogous to those of other insurgents before and since. In short, the Archduke’s assassination was a signal event in, if not the start of, a continuum in the history of modern terrorism.